PSTi8 with metformin ameliorates perimenopause induced steatohepatitis associated ER stress by regulating SIRT-1/SREBP-1c axis. Issue 12 (December 2020) - Singh, Pragati; Reza, Mohammad Irshad; Syed, Anees A.; Garg, Richa; Husain, Athar; Katekar, Roshan; Goand, Umesh K.; Riyazuddin, Mohammed; Gupta, Anand P.; Gayen, Jiaur R.
Abstract: Aims: Hepatic steatosis in women confronting menopause is the manifestation of substantial fructose consumption and forms a positive feedback loop to develop endoplasmic reticulum (ER) stress. Previously pancreastatin inhibitor peptide-8 (PSTi8) and Metformin (Met) combination effectively ameliorated hepatic lipid accumulation in high fructose diet (HFrD) fed diabetic mice models at reduced doses. Moreover, SIRT-1 plays a crucial role in the regulation of SREBP-1c. Hence we hypothesized that Met and PSTi8 in combination (at therapeutic lower doses) could mitigate hepatic steatosis linked ER stress by activating SIRT-1 and precluding SREBP-1c in HFrD fed 4-Vinylcyclohexenediepoxide (HVCD) induced perimenopausal rats. Main methods: HVCD rats were fed HFrD for 12 weeks, accompanied by 14 days of treatment with Met, PSTi8, and combination. We confirmed model establishment by estrus cycle study, estradiol level, and intraperitoneal glucose tolerance test. Plasma lipid profile and liver function were determined. Also, mRNA and protein expressions were examined. Moreover, distribution of SIRT-1 and SREBP-1c was detected in HepG2 cells by immunofluorescence staining. Key findings: HVCD group displayed augmented insulin resistance (IR), lipogenesis, and ER stress in the liver. Combination therapy improved the estrus cyclicity, estradiol, and lipid profile of HVCD rats. Met and PSTi8 combination reduced hepatic SREBP-1c and triggered SIRT-1 expression in high fructose-induced insulin-resistant HepG2 cells; consequently, combination therapy attenuated ER stress. Significance: Succinctly, present research promotes impetus concerning the remedial impact of Met with PSTi8 at lower therapeutic doses to ameliorate hepatic IR, steatosis, and associated ER stress by revamping the SIRT-1/SREBP-1c axis in perimenopausal rats. Abstract : Combination therapy (Met + PSTi8); PSTi8; Metformin; Hepatic steatosis; ER stress; SIRT-1; SREBP-1c; Perimenopausal rat